Accelerating fracture simulation with phase field methods based on Drucker-Prager criterion - Liu, Bin; Liu, Zhenghe; Yang, Lusheng (Frontiers in Physics, 2023)
The paper presents a framework for accelerating the phase field modeling of compressive failure of rocks. In this study, the Drucker-Prager failure surface is taken into account in the phase field model to characterize the tension-compression asymmetry of fractures in rocks. The degradation function that decouples the phase-field and physical length scales is employed, in order to reduce the mesh density in large structures. To evaluate the proposed approach, four numerical examples are given. The results of the numerical experiments demonstrate the accuracy and efficiency of the proposed approach in tracking crack propagation paths in rock materials under Drucker-Prager criterion.